TRADISI KEMANTEN SUNAT DESA LUMPUR KABUPATEN GRESIK 1960-2005 - PUTRI DANA ISWARA, LARAS; , SUMARNO (Jur. Pendidikan Sejarah FIS UNESA, 2019)
Tradition is a legacy from ancestors that is still preserved by future generations. Traditions carried out by somepeople have certain meanings and values. The values contained in the impementation of tradiions have messages or advicefor the people who run them. This research is included in qualitative research because it describes how the tradition ofKemanten Sunat in Lumpur village, Gresik and what are the factors causing alack of interest in the community to knowhow to implement and what causes reduced interest in the tradition of Kemanten Sunat using the method of interviewingtraditional practitioners, wuthnesses and society around as wellas documentation ocomplete the interview.Kata Kunci: Tradisional, Kemanten Sunat, Desa Lumpur